147k views
12 votes
I need answer ASAP
If f(x) = 2x+1 and g(x) = 3x-2 Find f[g(1)] =

User Slushi
by
5.2k points

1 Answer

0 votes

Answer:

f[g(1)] = 3

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

f(x) = 2x + 1

g(x) = 3x - 2

Step 2: Find g(1)

  1. Substitute in x: g(1) = 3(1) - 2
  2. Multiply: g(1) = 3 - 2
  3. Subtract: g(1) = 1

Step 3: Find f[g(1)]

  1. Substitute in g(1): f[g(1)] = 2(1) + 1
  2. Multiply: f[g(1)] = 2 + 1
  3. Add: f[g(1)] = 3
User Matt Rek
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.